Biopriming of Maize with their endophyte Aspergillus fumigatus reinforces their resistance to salinity stress and improves their physiological traits - Marwa A. Yassin; Nelly George; Lamis Shabaan; Yousra Gouda (BMC Plant Biology)
Abstract Zea mays L. (Maize) is one of the most crucial world’s crops, for their nutritional values, however, the water scarcity and consequent soil salinization are the major challenges that limit the growth and productivity of this plant, particularly in the semi-arid regions in Egypt. Recently, biopriming has been recognized as one of the most efficient natural-ecofriendly approaches to mitigate the abiotic salt stress on plants. The haploid (128) and triploid (368) seeds of maize were selected as model verities for assessing their resistance to salt stress and mitigating their effect by fungal-biopriming. Overall, the haploid and triploid plants viabilities were drastically affected by salt concentration, at 500 mM of NaCl. At 500 mM NaCl, the fresh weights of the triploid and haploid seedlings were reduced by ~ 5 and 6.1 folds, compared to the controls, ensuring slightly higher salt resistance of the triploid than haploid ones. The pattern of the endophytic fugal isolates was plausibly changed with the salt concentration for both plant types, Aspergillus fumigatus isolate was emerged with the higher NaCl concentration (400–500 mM), and their morphological identity was molecularly confirmed and deposited into Genbank with accession # PQ200673. The fungal bioprimed seeds of the haploid and triploid plants were irrigated with 400 mM NaCl. The fungal-bioprimed plants displayed a significant improvement on the shoot density, fibrous roots, root length, shoot length, and leaves numbers and areas of the stressed-plants by ~ 1.7 folds, compared to control, ensures the triggering of different salt resistance machineries in plants upon fungal biopriming. The total antioxidant enzymes activities “catalase, peroxidase, superoxide dismutase” of the salt-stressed bioprimed maize plants were increased by ~ 4.7–5.3%, compared to control, confirming the mitigating effect of the salinity stress on plants upon fungal biopriming. The chlorophyll and carotenoids contents were significantly increased of the salt stressed maize upon biopriming with A. fumigatus. The expression of the sod, apx2, nhx11, hkt1, H + -PPase, nced of the plant salt stressed was strongly increased in response to A. fumigatus biopriming, normalized to β-actin gene. The expression of apx2 was dramatically increased by about 30 and 43 folds, in response to fungal biopriming. The nhx1 was significantly up-regulated by 18.9 fold in response to fungal biopriming, compared to control.